BER Performance of IM/DD FSO System with OOK using APD Receiver - Petkovic, Milica I.; Dordevic, Goran T.; Milic, Dejan N. (Společnost pro radioelektronické inženýrství, 2014)
In this paper, the performance of intensity-modulated with direct detection (IM/DD) free space optical (FSO) system using the on-off keying (OOK) and avalanche photodiode (APD) receiver is observed. The gamma-gamma model is used to describe the effect of atmospheric turbulence since it provides good agreement in the wide range of atmospheric conditions. In addition, the same FSO system with equal gain combining applied at the reception is analyzed. After theoretical derivation of the expression for the bit error rate (BER), the numerical integration with previously specified relative calculation error is performed. Numerical results are presented and confirmed by Monte Carlo simulations. The effects of the FSO link and receiver parameters on the BER performance are discussed. The results illustrate that the optimal APD gain in the minimum BER sense depends considerably on the link distance, atmospheric turbulence strength and receiver temperature. In addition, the value of this optimal gain is slightly different in the case of spatial diversity application compared with single channel reception.
Keywords: Free space optical (FSO) communications; atmospheric turbulence; gamma-gamma distribution; error probability; avalanche photodiode (APD); on-off keying (OOK); equal gain combining (EGC)